The contrasted evolutionary fates of deep‐sea chemosynthetic mussels (Bivalvia, Bathymodiolinae)1. Issue 14 (31st October 2013) - Thubaut, Justine; Puillandre, Nicolas; Faure, Baptiste; Cruaud, Corinne; Samadi, Sarah
Abstract Bathymodiolinae are giant mussels that were discovered at hydrothermal vents and harboring chemosynthetic symbionts. Due to their close phylogenetic relationship with seep species and tiny mussels from organic substrates, it was hypothesized that they gradually evolved from shallow to deeper environments, and specialized in decaying organic remains, then in seeps, and finally colonized deep‐sea vents. Here, we present a multigene phylogeny that reveals that most of the genera are polyphyletic and/or paraphyletic. The robustness of the phylogeny allows us to revise the genus‐level classification. Organic remains are robustly supported as the ancestral habitat for Bathymodiolinae. However, rather than a single step toward colonization of vents and seeps, recurrent habitat shifts from organic substrates to vents and seeps occurred during evolution, and never the reverse. This new phylogenetic framework challenges the gradualist scenarios "from shallow to deep." Mussels from organic remains tolerate a large range of ecological conditions and display a spectacular species diversity contrary to vent mussels, although such habitats are yet underexplored compared to vents and seeps. Overall, our data suggest that for deep‐sea mussels, the high specialization to vent habitats provides ecological success in this harsh habitat but also brings the lineage to a kind of evolutionary dead end.